Lessons Learned From the Historical Trends on Thrombolysis Use for Acute Ischemic Stroke Among Medicare Beneficiaries in the United States - Meng, Tong; Trickey, Amber W.; Harris, Alex H. S.; Matheson, Loretta; Rosenthal, Sarah; Traboulsi, Abd Al-Rahman; Saver, Jeffrey L.; Wagner, Todd; Govindarajan, Prasanthi (Frontiers in Neurology, 2022)
Background The most recent time trends on intravenous thrombolysis (IVT) utilization for acute ischemic stroke was reported in 2011 using the Get with the Guidelines. Our objectives are to assess and validate the change in IVT utilization through 2014 in a national sample of Medicare beneficiaries and to examine the effect of patient, stroke center designation, and geography on IVT utilization. Methods We built a comprehensive national stroke registry by combining patient-level, stroke center status, and geographical characteristics, using multiple data sources. Using multiple national administrative databases from 2007 to 2014, we generated a mixed-effect logistic regression model to characterize the independent associations of patient, hospital, and geographical characteristics with IVT in 2014. Results Use of IVT increased consistently from 2.8% in 2007 to 7.7% in 2014, P < 0.001. Between group differences persisted, with lower odds of use in patients who were ≥86 years (aOR 0.74, 95% CI 0.65–0.83), Black (aOR 0.73, 95% CI 0.61–0.87), or treated at a rural hospital (aOR 0.88, 95% CI 0.77–1.00). Higher odds of use were observed in patients who arrived by ambulance (aOR 2.67, 95% CI 2.38–3.00), were treated at a hospital certified as a stroke center (aOR 1.96, 95% CI 1.68–2.29), or were treated at hospitals located in the most socioeconomically advantaged areas (aOR 1.27, 95% CI 1.05–1.54). Conclusions Between 2007 and 2014, the frequency of IVT for patients with acute ischemic stroke increased substantially, though differences persisted in the form of less frequent treatment associated with certain characteristics. These findings can inform ongoing efforts to optimize the delivery of IVT to all AIS patients nationwide.